Морфо-функциональные особенности пищеварительной системы клеща Phytoseiulus persimilis Athias-Henriot (Gamasoidea, Phytoseiidae) - Акимов, И.А.; Старовир, И.С. (Вестник зоологии, 1974)
Morpho-functional changes in the alimentary canal epithelium and the process of food digestion are studied in mites. The changes in the epithelial cells of the midgut are shown to come very rapidly. Each 10-15 min. digestive cells degenerate. They are replaced by non-differentiated cells. The formation, growth and decomposition of digestive granules are observed in the digestive cells.